Law & ethics for medical careers - Judson, Karen; Harrison, Carlene (Boston, Massachusetts : McGraw Hill Education, 2010)
Laws & Ethics for Medical Careers, Fifth Edition, provides an overview of the laws and ethics you should know to help you give competent, compassionate care to patients that is within acceptable legal and ethical boundaries. The text can also serve as a guide to help you resolve the many legal and ethical questions you may reasonably expect to face as a student and, later, as a health care practitioner. The text features legal cases, anecdotes, and sidebars pertinent to health-related careers. Content has been updated and special attention has been paid to legislation affecting heath care.
Introduction to law and ethics -- Working in health care -- Law, the courts, and contracts -- Professional liability and medical malpractice -- Defenses to liability suits -- Medical records and informed consent -- Privacy law and HIPAA -- Physicians' public duties and responsibilities -- Workplace legalities -- The beginning of life and childhood -- Death and dying -- Health care trends and forecasts.
Includes bibliographical references and index.
Keywords: ETHICS, MEDICAL